2021
DOI: 10.1136/jech-2021-216732
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of anxiolytics, sedatives, hypnotics and antidepressants in outpatient, universal care during the COVID-19 pandemic in Portugal: a nationwide, interrupted time-series approach

Abstract: BackgroundThe COVID-19 pandemic has had a significant impact on the population’s mental health. However, its impact on the consumption of anxiolytics, sedatives, hypnotics and antidepressants remains to be evaluated. Hence, this article aims to assess the prescription trends of these drugs in Portugal, from January 2018 to March 2021, while critically examining whether the COVID-19 pandemic had an impact on these prescription trends or not.MethodsA nationwide interrupted time-series analysis of the prescriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
25
3
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 26 publications
8
25
3
8
Order By: Relevance
“…Namely, the COVID-19 pandemic was not associated with an immediate increase in antidepressant prescription fills, but it was associated with an increase over time and is expected to continue increasing in the near future. The increased incident rate of antidepressant fills during the pandemic in Israel is consistent with prior reports that used nationwide data from the Europe and the USA (Estrela et al, 2022 ; Express Scripts, 2020 ; Rabeea et al, 2021 ) and aligns with similar findings following other events producing population-level distress, such as terrorist attacks (Druss & Marcus, 2004 ) and earthquakes (Trifirò et al, 2013 ). The increased antidepressant fill rate during the pandemic was higher than that seen during the Gaza war, probably reflecting the greater length, morbidity, and mortality associated with the pandemic.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Namely, the COVID-19 pandemic was not associated with an immediate increase in antidepressant prescription fills, but it was associated with an increase over time and is expected to continue increasing in the near future. The increased incident rate of antidepressant fills during the pandemic in Israel is consistent with prior reports that used nationwide data from the Europe and the USA (Estrela et al, 2022 ; Express Scripts, 2020 ; Rabeea et al, 2021 ) and aligns with similar findings following other events producing population-level distress, such as terrorist attacks (Druss & Marcus, 2004 ) and earthquakes (Trifirò et al, 2013 ). The increased antidepressant fill rate during the pandemic was higher than that seen during the Gaza war, probably reflecting the greater length, morbidity, and mortality associated with the pandemic.…”
Section: Discussionsupporting
confidence: 88%
“…The use of antidepressant medication during the pandemic provides complementary information, focused on the intersection between help-seeking behavior and service provision. Studies of antidepressant use derived from large-scale nationwide datasets are few, but those from Europe and the USA provide convincing evidence of increased antidepressant prescription pharmacy claims during the pandemic compared to the pre-pandemic period (Estrela et al, 2022 ; Express Scripts, 2020 ; Rabeea, Merchant, Khan, Kow, & Hasan, 2021 ), and suggest significant moderating effects for sex and age (NHS Digital, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the minor decline in the number of DHD for anti-depressants, similar results were found in a study carried out in Portugal ( Estrela et al, 2021 ). According to another study conducted in Aragon ( Mestre, 2021 ), the follow-up period used for our study (6 months following the end of the lockdown) may be insufficient for the detection of changes in the consumption of these drugs.…”
Section: Discussionsupporting
confidence: 86%
“…In Germany [25], a decrease in the prescription of drugs for mental disorders was identified. Interestingly, similarly to this study, research from Portugal found no impact of the pandemic on the increasing prescribing trends of drugs of interest [26].…”
Section: Discussionsupporting
confidence: 81%